2009
DOI: 10.1186/gb-2009-10-9-r102
|View full text |Cite
|
Sign up to set email alerts
|

Comparative genome and phenotypic analysis of Clostridium difficile 027 strains provides insight into the evolution of a hypervirulent bacterium

Abstract: Clostridium difficile virulence evolution

A genome comparison of non-epidemic and epidemic strains of Clostridium difficile reveals gene gains that could explain how a hypervirulent strain has emerged

Abstract Background: The continued rise of Clostridium difficile infections worldwide has been accompanied by the rapid emergence of a highly virulent clone designated PCR-ribotype 027. To understand more about the evolution of this virulent clone, we made a three-way genomic and phenotypic comparison of a…
Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

19
460
1
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 425 publications
(496 citation statements)
references
References 69 publications
19
460
1
1
Order By: Relevance
“…630 (RT 012), mobile elements accounted for ~10% of the genome and included a plasmid, prophages, transposons, IStrons, genomic islands, CRISPRs and a skin element (Sebaihia et al, 2006). This has remained consistent in the annotated genomes of other strains published since, including M120 (clade 5), and R20291 (clade 2) (He et al, 2010;Stabler et al, 2009). …”
Section: Accepted Manuscriptmentioning
confidence: 64%
“…630 (RT 012), mobile elements accounted for ~10% of the genome and included a plasmid, prophages, transposons, IStrons, genomic islands, CRISPRs and a skin element (Sebaihia et al, 2006). This has remained consistent in the annotated genomes of other strains published since, including M120 (clade 5), and R20291 (clade 2) (He et al, 2010;Stabler et al, 2009). …”
Section: Accepted Manuscriptmentioning
confidence: 64%
“…It was reported that TcdA is relatively well conserved, while TcdB has much variability, 38,39 especially the RBD region. 38 The N terminus encompassing the GTD and CPD domains is more conserved between historical and epidemic strains.…”
Section: Discussionmentioning
confidence: 99%
“…C. difficile strains R20291 (Stabler et al, 2009), CD646 (Keel et al, 2007), JIR8094 (O'Connor et al, 2006) and the gluD mutants (Table 1) were grown anaerobically (10 % H 2 , 10 % CO 2 and 80 % N 2 ) in TY (tryptose yeast extract) broth or TY agar as described previously (Dupuy & Sonenshein, 1998). Escherichia coli strain S17-1 (Teng et al, 1998) used for conjugation was cultured aerobically in LB and supplemented with chloramphenicol (30 mg ml 21 ) or ampicillin (100 mg ml 21 ), when needed.…”
Section: Methodsmentioning
confidence: 99%